Application of the steady-state intestinal perfusion system in measuring intestinal fluid absorption and bicarbonate secretion in vivo - Fan, Wenjuan; Tan, Qinghai (Frontiers in Physiology, 2023)
Background: The steady-state intestinal perfusion system represents a tool used in measuring intestinal fluid absorption and bicarbonate secretion in vivo; however, detailed procedures and parameters were not elucidated fully. Aim: We focused on the methods of the steady-state intestinal perfusion system comprehensively including the blood pressure, hematocrit, blood gas, and heart rate of mouse. Methods: Anesthetized, tracheally intubated, and artificially ventilated mice were used for this system. The blood pressure, hematocrit, blood gas, heart rate, and rate of fluid absorption and HCO3- secretion of the small intestine and colon at different time points were evaluated. Results: Blood pressure, hematocrit, blood gas, and heart rate became stable at the 30 min time point after completion of surgery and could be maintained for 2 h. Rates of fluid absorption and bicarbonate secretion were also kept stable during the period of steady state of mice. Rates of fluid absorption and bicarbonate secretion were different among the jejunum, ileum, proximal, and mid-distal colon. Conclusion: The steady-state intestinal perfusion system is a reliable system for measuring intestinal fluid absorption and bicarbonate secretion in vivo.